Combating Trans-Border Banditry and Security Issues in Katsina State, Nigeria: Challenges and Strategies - Momoh, Salifu Achile; Adadu , Yahaya Abdullahi; Caleb, Ruth (Kashere Journal of Politics and International Relations, 2025)
This research investigates the complex phenomenon of trans-border banditry and security in Katsina State, Nigeria. It contextualises the challenges posed by geographical proximity to Niger Republic, socio-economic instabilities, and institutional inadequacies. The research questions focus on evaluating the effectiveness of measures taken by government to fight the menace and identifying key impediments to their success. Objectives of the study includes; assessing security strategies and exploring socio-economic, political, and institutional factors contributing to the issue. Employing a mixed-methods methodology, the study collects quantitative data via structured questionnaires and qualitative insights through key informant interviews. Analyses reveal that while initiatives like vigilante groups and increased border patrols have achieved some successes. Thematic findings indicate that community engagement and local intelligence are pivotal, yet underutilized in combating trans-border banditry in Katsina State. Additionally, the ECOWAS free movement protocol and weak regional partnerships exacerbate border control issues. Key findings highlight the effectiveness of punitive measures such as prosecutions but reveal public skepticism toward softer approaches like bandit rehabilitation. Conclusions underscore the need for enhanced security collaboration, advanced surveillance technologies, and economic empowerment programs. Recommendations advocate for robust community policing, capacity-building for security forces, and regional agreements to address the transnational nature of the crisis. Ultimately, sustainable peace in Katsina requires addressing root causes of transborder crimes, strengthening institutional frameworks, and fostering trust between security agencies and affected communities.